The Nature of Pictorial Representations - Ferretti, Gabriele (Phenomenology and Mind, 2018)
A crucial question in the study of picture perception asks about whether, when perceiving an object in a picture, we see only the depicted scene or, rather, we simultaneously see both the depicted scene and the surface. Two different views have fueled the debate since a long time. According to Wollheim, we see both the depicted scene and the picture’s surface simultaneously. Call this the ‘simultaneous account of picture perception’ (SA). SA is in contrast with Gombrich’s view that, during picture perception, we do not simultaneously see both the depicted scene and the surface, but we alternate between these two visual states. Call this the ‘non-simultaneous account of picture perception’ (NA). The debate between these two positions still persists in the contemporary literature on picture perception. In this paper, I first analyze the notion of vision SA and NA are committed to. Then, by discussing empirical evidence from vision science, I offer an argument that supports SA.